2021
DOI: 10.3390/ijms222413218
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Sensitive Hypertension in GR+/− Rats Is Accompanied with Dysregulation in Adrenal Soluble Epoxide Hydrolase and Polyunsaturated Fatty Acid Pathways

Abstract: Mutations within the glucocorticoid receptor (GR) gene locus lead to glucocorticoid resistance which is characterized by several clinical symptoms such as adrenal gland hyperplasia and salt-sensitive hypertension, although the underlying mechanisms are still unknown. We studied GR haploinsufficient (GR+/−) Sprague Dawley rats which, on a standard diet, showed significantly increased plasma aldosterone and corticosterone levels and an adrenocortex hyperplasia accompanied by a normal systolic blood pressure. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…45 Study on the major pathways of hypertension has shown that the haploidy insufficiency of glucocorticoid receptor in rats can cause the disorder of linoleic acid metabolism pathway. 57 Another study on the mechanism of melatonin-mediated hypotension, at 18 h, melatonin acted on the (cGMP-PKG) signaling pathway involved in NO synthesis, suggesting that the regulation of blood pressure could be achieved through the cGMP-PKG signaling pathway. 118 According to KEGG pathway analysis of diabetes, there are drug metabolism-cytochrome P450, linoleic acid metabolism and Neuroactive ligand-receptor interaction, et al Hogan et al used quantitative reverse transcription Quantitative Real-time polymerase chain reaction (QRT-PCR) to identify differentially regulated gene expression of islet amyloid, which is associated with islet physiology and pathology of type II diabetes mellitus, and found that it contains steroidogenic acute regulatory protein (STAR protein), which is part of the synthetic response group of steroid hormone metabolism.…”
Section: Mechanism and Components Of M Oleifera In Preventing And Tre...mentioning
confidence: 99%
“…45 Study on the major pathways of hypertension has shown that the haploidy insufficiency of glucocorticoid receptor in rats can cause the disorder of linoleic acid metabolism pathway. 57 Another study on the mechanism of melatonin-mediated hypotension, at 18 h, melatonin acted on the (cGMP-PKG) signaling pathway involved in NO synthesis, suggesting that the regulation of blood pressure could be achieved through the cGMP-PKG signaling pathway. 118 According to KEGG pathway analysis of diabetes, there are drug metabolism-cytochrome P450, linoleic acid metabolism and Neuroactive ligand-receptor interaction, et al Hogan et al used quantitative reverse transcription Quantitative Real-time polymerase chain reaction (QRT-PCR) to identify differentially regulated gene expression of islet amyloid, which is associated with islet physiology and pathology of type II diabetes mellitus, and found that it contains steroidogenic acute regulatory protein (STAR protein), which is part of the synthetic response group of steroid hormone metabolism.…”
Section: Mechanism and Components Of M Oleifera In Preventing And Tre...mentioning
confidence: 99%
“…A high salt diet induced furthermore an increase of corticosterone excretion and the BP in these mice. Similarly, rats with GR haploinsufficiency (GR +/em2 , [ 68 ]) when kept on a standard diet showed significantly increased plasma aldosterone and corticosterone levels and an adrenocortex hyperplasia but a normal systolic blood pressure. Salt-sensitive hypertension was only provoked in combination with high salt intake in the transgenic rats [ 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, rats with GR haploinsufficiency (GR +/em2 , [ 68 ]) when kept on a standard diet showed significantly increased plasma aldosterone and corticosterone levels and an adrenocortex hyperplasia but a normal systolic blood pressure. Salt-sensitive hypertension was only provoked in combination with high salt intake in the transgenic rats [ 68 ]. During prolonged salt exposure, both transgenic and control rats progressively reduced their salt intake [ 68 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations